Impact of pupil size on defocus curve, contrast sensitivity, and patient satisfaction in a diffractive, simultaneous vision intraocular lens - Petra Davidova; Klemens Paul Kaiser; Tyll Jandewerth; Eva Hemkeppler; Myriam Böhm; Tom Struller; Thomas Kohnen (Journal of Cataract & Refractive Surgery, 2026)
Purpose: To evaluate the relationship between pupil size (PS) and defocus curve, contrast sensitivity (CS), spectacle independence, and patient satisfaction after implantation of a diffractive, simultaneous vision intraocular lens (SVL; AcrySof IQ PanOptix). Setting: Department of Ophthalmology, Goethe-University, Frankfurt, Germany. Design: Post hoc analysis of prospective studies. Methods: Patients were included 3 months after bilateral implantation of a diffractive SVL. Exclusion criteria included any ocular pathologies or previous ocular surgeries besides cataract or refractive lens exchange. Monocular defocus curve and infrared-based pupillometry (PupilX) in mesopic (MC) and photopic conditions (PC) and binocular visual acuity (VA) in various distances, CS, satisfaction in daily activities (driving day/night, TV, theater, home, PC, newspaper, cooking, and domestic work), and spectacle independence for distance, intermediate, and near were obtained. PS was analyzed continuously and categorized in small (≤4 mm [MC]; ≤2.5 mm [PC]), medium (>4 to 5 mm [MC]; >2.5 to 4 mm [PC]), and large (>5 mm [MC]; >4 mm [PC]). Results: 52 patients (mean age 68 years) were included. 3 months postoperatively, PS was 4.24 (2.60 to 6.10) mm in MC and 3.38 (1.20 to 5.60) mm in PC. Besides correlations with extreme ends of the defocus curve, especially photopic PS weakly correlated with near-visual and partially with the intermediate range. Smaller photopic PS led partially to more near-spectacle independence. Photopic and mesopic PS moderately correlated with range of depth-of-field (RoF) ≤0.2 and 0.3 logMAR. Smaller pupils yielded better VA across the defocus curve, bigger RoF, and a trend of being more satisfied with newspaper reading. In the other parameters, PS was not significant. Conclusions: PS especially affected the near-visual range, near-spectacle independence, and RoF in a diffractive, SVL.